CYBERSECURITY ASSESSMENT FRAMEWORK (TANZANIA CASE STUDY) - Haji Juma, Abassi
This study addresses the critical issue of cybersecurity readiness in Tanzania, where a growing cybercrime threat landscape exposes organizations due to gaps in existing cybersecurity frameworks. These gaps are further amplified by the lack of user knowledge on digital technology, making them more susceptible to cyberattacks. This study addresses the problem by proposing improvements to Lubua’s Cybersecurity Policy Framework. These improvements incorporate components from established international standards like ISO 27001 and NIST CSF. The study employs Design Research methodology (DRM). The "Prescriptive study" phase involved developing a new cybersecurity assessment framework (Table IV.1). The "Descriptive study II" phase entailed a descriptive analysis of this framework, focusing on its alignment with key aspects crucial for success in the Tanzanian context: Alignment with Local